2022
DOI: 10.1109/access.2021.3138775
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors of Component-Based Software Outsourcing Development From Vendors’ Perspective: A Systematic Literature Review

Abstract: Component-Based Software Development (CBSD) is a very demanding approach for developing complex products or systems. In CBSD, software or product is creating from reusable pieces of components. With the help of CBSD, a complex system or software is developed with high quality, security, and within limited time and cost. However, this research will convince the outsourcing vendor organization to adopt the component software development using the CBSD approaches. A Systematic Literature Review (SLR) is used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The relevant attributes are tested in this research using the Chi-Square attributes selection technique [ 35 ]. The most important attributes establish a link between two categorical variables, specifically, a period, which is a relationship between observed and predicted frequency.…”
Section: Data Preprocessing and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The relevant attributes are tested in this research using the Chi-Square attributes selection technique [ 35 ]. The most important attributes establish a link between two categorical variables, specifically, a period, which is a relationship between observed and predicted frequency.…”
Section: Data Preprocessing and Methodologymentioning
confidence: 99%
“…Short decision tree models, each with a single decision point, were used in the development of AdaBoost. Decision stumps are the common name for such short trees [ 35 ]. Bootstrap Aggregation, often known as Bagging, is an ensemble technique for regression and classification.…”
Section: Data Preprocessing and Methodologymentioning
confidence: 99%
“…This paper explained almost all the applications, future technology for the IoT, and related challenges in more detail for the healthcare system, COVID-19, and future pandemics. In the future, Systematic Literature Review (SLR) [ 104 , 105 ] will be used to further explain each and every factor of the IoT related to healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Within the inter-organizational challenges, relationships with several environmental entities such as the insurance system, private partners and customers seemed to be crucial in implementing an efficient process of outsourcing in healthcare units (21,29). Despite the common misconception, one study showed that the relationships between such inter-organizational entities are much more integrated and connected to each other than intra-organizational relationships (30), a finding that clearly states the inter-connected nature of the realm in which any malfunction in the process related to each entity acts like a domino and paves the way for a total failure in the process of service delivery, a phenomenon which was narrated by several studies probing the challenges in the process of outsourcing (27)(28)(29)31). As this study foundcomplexities in rural areas as a major inter-organizational challenge faced during the process of outsourcing (29), Some researches have proposed the mainly impoverished low to middle income attribute of the society living in the rural areas as a major contributing factor resulting in an inefficient and ineffective outsourcing process, such phenomenon can be traced back to the fact that after the process of outsourcing which arguably results in higher costs of services for customers, the outsourced units expose to a diminished number of customers due to the lower socioeconomic level of the rural population (32,33); Moreover, staff with higher expertise and higher level of technologies seem to be harder to get employed in rural areas due to the costly nature of such inputs while the outsourced units in the rural areas lack the needed funds and the desired attractiveness to obtain such resources added with the lack of desirability from the side of private partners to cooperate in such risky circumstances (23,27).…”
Section: Discussionmentioning
confidence: 99%